Transvenous Cardiac Pacemaker Educational Resource - Jmir Cousar; Michael Bohanske; Jeffery Hill (Association of American Medical Colleges, 2015)
Abstract Transvenous cardiac pacemaker placement is an important and complex emergency procedure. Given that placement of a transvenous pacemaker is a relatively uncommon occurrence, maintaining procedural competency can be a considerable challenge. Utilizing principles of cognitive load theory, this educational resource provides a means for learning the procedure and maintaining clinical competence. This is accomplished through multiple learning activities including a procedural slide set, first-person point-of-view walkthrough video, and a procedural checklist, which allow for self-directed study and quick reference. This resource is clinically significant for practicing physicians, residents, and medical students attempting to gain or maintain competency with transvenous cardiac pacemaker placement.